Reading the visual - Serafini, Frank (Teachers College press, 2013)
Includes bibliographical references and index.; Introduction -- A multimodal world -- Why teachers and literacy educators should read this book -- What influenced me to write this book -- How this book is organized -- Part I: theoretical and instructional foundations -- 1. Multimodal ensembles -- So what exactly is a multimodal ensemble? -- Text, image, and design -- How modes work -- Multimodal or multimedia -- The discovery of the obvious -- Why should educators care about multimodal texts? -- Concluding remarks -- 2. Visual literacy, media literacy, and multiliteracies -- Defining literacy -- Visual literacy -- Media literacy -- Multiliteracies -- Concluding remarks -- 3. Foundational processes -- Foundational processes -- Perception -- Representation -- Interpretation -- Ideology -- Frameworks for interpreting visual images and multimodal ensembles -- Concluding remarks -- 4. Understanding multimodality -- Multimodality -- Sociocultural dimensions of multimodality -- Research on multimodality -- Essential aspects of multimodality -- Concluding remarks -- 5. Elements of art, design, and visual composition -- Elements of visual art -- Elements of multimodal ensembles -- Elements of visual grammar -- Concluding remarks -- Part II: curricular frameworks and pedagogical approaches -- 6. Picturebooks and picturebook theories -- Defining the picturebook -- Elements of picturebooks -- Picturebook codes -- Text-image relationships -- Art and the picturebook -- Postmodern influences on the picturebook -- Concluding remarks -- 7. Exploring multimodal ensembles: an example -- Piggybook from a perceptual analytical perspective -- Piggybook from a structural analytical perspective -- Piggybook from an ideological analytical perspective -- Concluding remarks -- 8. Curricular and pedagogical frameworks -- A curricular framework -- Defining units of study -- An instructional template -- Concluding remarks -- Part III: units of study -- Exploring postmodern picturebooks -- Exploring wordless picturebooks -- Exploring historical fiction picturebooks -- Exploring informational picturebooks -- Exploring illustrated novels -- Exploring graphic novels, comics, and cartoons -- Exploring advertisements -- Exploring news reports -- Exploring film -- Exploring digital media -- Epilogue: to see or not to see -- Developing and enlightened eye with our students -- Words and pictures and something in between -- Interpretation and representation -- The journey continues.; Reading the Visual is an essential introduction that focuses on what teachers should know about multimodal literacy and how to teach it. This engaging book provides theoretical, curricular, and pedagogical frameworks for teaching a wide-range of visual and multimodal texts, including historical fiction, picture books, advertisements, websites, comics, graphic novels, news reports, and film. Each unit of study presented contains suggestions for selecting cornerstone texts and visual images and launching the unit, as well as lesson plans, text sets, and analysis guides. These units are designed to be readily adapted to fit the needs of a variety of settings and grade levels.